The contribution of teledentistry in detecting tooth erosion in patients with eating disorders. (May 2021) - Giraudeau, Nicolas; Camman, Paul; Pourreyron, Laurence; Inquimbert, Camille; Lefebvre, Patrick
Objective: The aim of this study was to demonstrate that including a teledentistry consultation in the standard care provided to patients in an eating disorder day hospital could be beneficial, notably for screening for particular pathologies and preventing dental erosion. Methods: We included 50 patients from the eating disorders unit of the University Hospital of Montpellier, all of whom underwent a dental examination using asynchronous telemedicine. We recorded the data using teledentistry software for the medical file and an intraoral camera for the clinical videos. Remote diagnosis was performed using the Basic Erosive Wear Examination index. In addition, the participants completed a questionnaire to assess their risk factors for dental pathologies. Results: We found dental erosion in 92% of the patients, and 50% had at least one tooth with BEWE 2 or 3 type erosion. Conclusions: Despite the fact that there can be wide variety within a group of individuals with similar risk factors, dental telemedicine could promote awareness within this at-risk population, as well as provide personalised prevention advice to each patient. Above all, it would make it possible to treat these patients' lesions at the earliest possible moment, thereby improving their outcomes.